2023
DOI: 10.5455/ovj.2023.v13.i7.1
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological safety and quality survey of some dairy confectioneries with cream filling and topping

Abstract: Background: Dairy confectionaries are recently categorized as an important part of different consumers’ diets with increasing demand for cream-based cakes “Tourta” and gateau which are used as celebrating food for almost all occasions and celebrations. Aim: The study was designed for evaluating general quality and safety of such products. Methods: 100 cream-based (for topping and filing) samples; 50 cakes “Tourta” and 50 gateau, were purchase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Different ingredients used for preparing filling cream are whipped and gave cream with pH level 6.6, this level is considered as neutral pH values. Thus, most of microorganisms especially pathogenic bacteria can grow well and make the cream unsafe or could be hazardous (ICMSF, 1980 ;Abdelrasoul et al, 2023) Also, Sharifzadeh et al (2016) found that in 1993, the highest rate of food poisoning (15.5%) was caused by excellent bakery items with unbaked filling. In addition to the suitable pH level of cream, used milk powder in the recipe of cream, which is sensitive ingredients may be made cream.…”
Section: Hazard Analysis and Control Measures Of Raw Materials And Pr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Different ingredients used for preparing filling cream are whipped and gave cream with pH level 6.6, this level is considered as neutral pH values. Thus, most of microorganisms especially pathogenic bacteria can grow well and make the cream unsafe or could be hazardous (ICMSF, 1980 ;Abdelrasoul et al, 2023) Also, Sharifzadeh et al (2016) found that in 1993, the highest rate of food poisoning (15.5%) was caused by excellent bakery items with unbaked filling. In addition to the suitable pH level of cream, used milk powder in the recipe of cream, which is sensitive ingredients may be made cream.…”
Section: Hazard Analysis and Control Measures Of Raw Materials And Pr...mentioning
confidence: 99%
“…Resource Extraction Site (RES) unsafe or hazardous, since the milk powder could be a source of Salmonella Typhi. Abdelrasoul et al (2023) and El-Kadi et al (2018) stated that dairy products accounted for 4% of a total of 500 outbreak of human salmonellosis during the 10-year period.…”
Section: Hazard Analysis and Control Measures Of Raw Materials And Pr...mentioning
confidence: 99%